Protective effects of carotenoids from saffron on neuronal injury in vitro and in vivo - Ochiai, Takashi; Shimeno, Hiroshi; Mishima, Ken-ichi; Iwasaki, Katsunori; Fujiwara, Michihiro; Tanaka, Hiroyuki; Shoyama, Yukihiro; Toda, Akihisa; Eyanagi, Reiko; Soeda, Shinji (Biochimica et biophysica acta, 2007)
Crocus sativus L. (saffron) has been used as a spice for flavoring and coloring food preparations, and in Chinese traditional medicine as an anodyne or tranquilizer. Our previous study demonstrated that crocin, a carotenoid pigment of saffron, can suppress the serum deprivation-induced death of PC12 cells by increasing glutathione (GSH) synthesis and thus inhibiting neutral sphingomyelinase (nSMase) activity and ceramide formation. The carotenoid pigments of saffron consist of crocetin di-(β- d-glucosyl)-ester [dicrocin], crocetin-(β- d-gentiobiosyl)-(β- d-glucosyl)-ester [tricrocin] and crocetin-di-(β- d-gentiobiosyl)-ester [crocin]. Saffron also contains picrocrocin, the substance causing saffron's bitter taste. In this study, to confirm whether neuroprotective effects of saffron are caused solely by crocin, we examined the antioxidant and GSH-synthetic activities of these crocins in PC12 cells under serum-free and hypoxic conditions. Measurements of cell viability, peroxidized membrane lipids and caspase-3 activity showed that the rank order of the neuroprotective potency at a concentration of 10 μM was crocin > tricrocin > dicrocin and picrocrocin (the latter two crocins had a little or no potency). In addition, we show that among these saffron's constituents, crocin most effectively promotes mRNA expression of γ-glutamylcysteinyl synthase (γ-GCS), which contributes to GSH synthesis as the rate-limiting enzyme, and that the carotenoid can significantly reduce infarcted areas caused by occlusion of the middle cerebral artery (MCA) in mice.